A Randomized Comparative Study of Attenuation of The Pressure Response and Ease of Insertion to Awake Fibreoptic Intubation with Dexmedtomidine Infusion Alone Vs Fentanyl and Midazolam Infusion - Balwinder Kaur Rekhi; Singh H; Kaur A; Kaur J (GMC Patiala Journal of Research and Medical Education, 2018)
When performing awake fibreoptic intubation, anesthesiologists may find it difficult to provide enough sedation for patient to be comfortable and cooperative one at the same time avoiding airway compromise from too much sedation. The ideal sedation provides patient comfort and maintenance of spontaneous respiration smooth intubation conditions amnesia and stable hemodynamic.